Perbandingan Strategi Penanganan Pandemi Covid-19 di Indonesia dan Malaysia - Putri, Shelvia Arnie; Dompak, Timbul (LPPM Universitas Putera Batam, 2024)
Countries' reactions to the global pandemic vary greatly. Public support and government policies are crucial to managing the pandemic's success. It has a significant economic impact as it has been challenged for some time by several countries. However, some countries are also dealing well enough to prevent an increase in Covid-19 cases and protect their economies. Malaysia is among the countries that, along with New Zealand, Taiwan, and China, have the honorable ability to curb the spread of the virus and restore economic normality in the face of the Covid-19 epidemic. This article explains how the country's capacity is capable of becoming a major capital in dealing with the pandemic in Malaysia. Adequate state capacity will be able to generate public confidence so that that confidence can be a catalyst for successful policy implementation. In addition to national capacity, leadership aspects at the national and local levels play an important role in supporting the success of government policies. Effective leadership can promote a favourable atmosphere for public adherence to government policies. Like a common enemy, the support of community elements is crucial to success against the spread of the virus.